TEKNOLOGI INFORMASI DAN KOMUNIKASI DI PENDIDIKAN DASAR: STUDI LITERATUR DAN PERBANDINGAN IMPLEMENTASI ANTARNEGARA (SINGAPURA, FINLANDIA, DAN INDONESIA) - Abdul Haris; Anisatul Basiroh; Dende Bida Asmarawati; Dewi Trisnawati; Duwi Yuliawati; Hadijah; Yulina Eva Riany (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Information and Communication Technology (ICT) integration has become the primary cornerstone and epistemological catalyst for global primary education transformation. Through a systematic literature review of ten contemporary scientific articles (2020–2025) indexed in SINTA and Scopus, this study critically analyzes the trends, benefits, and structural implementation barriers of digitalization in primary schools. Findings indicate that adopting interactive media, artificial intelligence, and augmented reality significantly enhances student motivation, cognitive engagement, and learning outcomes. Nevertheless, persistent regional infrastructure disparities and low teacher digital literacy emerge as the primary structural constraints in the field. Comparative macro-analysis among Singapore, Finland, and Indonesia underscores that while physical infrastructure fulfillment and digital suprastructures are mandatory, they do not stand alone. Rather, teachers' pedagogical readiness—anchored in the Technological Pedagogical Content Knowledge (TPACK) framework—and the reinforcement of critical media literacy serve as the ultimate determinants driving the success, equitable access, and long-term sustainability of educational digital transformation.